The Effect of Financial Literacy and Payment Gateway on Financial Performance in MSMEs in Palembang City - Dwiana, Handina; Gunarto, Muji (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research, aimed at testing the influence of financial literacy and payment gateways on the financial performance of MSMEs in Palembang, yields significant findings. The sampling technique, non-probability with purposive sampling, was employed to gather data from 100 respondents in the culinary subsector MSMEs in Palembang. The research method, a quantitative approach involving the distribution of questionnaires, was used. The data analysis, facilitated by SmartPLS 3 software, included the evaluation of measurement models, structural models (inner models), and hypothesis testing. The research results, which are of paramount importance, reveal that financial literacy has a positive and significant effect on financial performance, payment gateway has a negative and insignificant effect on financial performance, financial literacy has a positive and significant effect on payment gateways, and payment gateways are unable to mediate and have a negative impact between financial literacy and financial performance